Run the storm : a savage hurricane, a brave crew, and the wreck of the SS El Faro - Foy, George (Scribner, 2018)
In the best-selling tradition of A Perfect Storm and The Finest Hours, a harrowing account of the incredible true story of the recent shocking disappearance of El Faro, a gigantic American cargo ship that disappeared in Hurricane Joaquin and sank suddenly in the Bermuda Triangle in 2015--taking with it 33 lives.